A Passive Shield for the RED-100 Neutrino Detector; Instruments and Experimental Techniques; Vol. 64, iss. 2 - Akimov D. Yu. Dmitry Yurjevich; Aleksandrov I. S. Ivan Sergeevich; Belov V. A. Vladimir Aleksandrovich; Efremenko Yu. V. Yury Valentinovich; Etenko A. V. Aleksandr Vladimirovich (2021, 2021)
Title screen